The effect of nursing interventions based on burns wean assessment program on successful weaning from mechanical ventilation: A randomized controlled clinical trial - Maryam Sepahyar; Shahram Molavynejad; Mohammad Adineh; Mohsen Savaie; Elham Maraghi (Wolters Kluwer Medknow Publications, 2021)
Background: The effective design and implementation of the nursing interventions to evaluate the patients' readiness for ventilator weaning will reduce their connection time to the ventilator and the complications of their connection to it. This study was conducted to examine the effect of nursing interventions based on the Burns Wean Assessment Program (BWAP) on successful weaning from Mechanical Ventilation (MV). Materials and Methods: In this clinical trial, 70 patients undergoing MV in the Intensive Care Units (ICUs) of Golestan Hospital (Ahvaz, Iran) in 2018 were randomly assigned to intervention and control groups. The nursing interventions designed based on BWAP were implemented on the patients in the intervention group, who were later weaned from the device according to this program. The recorded data included demographic information, BWAP score, vital signs, and laboratory values, which were analyzed using the Pearson correlation coefficient, Chi-Square, Fisher, and Mann-Whitney U tests. Results: There was a statistically significant and inverse correlation between the BWAP score and the MV duration such that a high BWAP score was associated with a shorter MV time (p = 0.041). Also, the mean number of re-intubation (p = 0.001) and the number of re-connection to the ventilator in the intervention group were significantly lower (p = 0.005). Conclusions: The results showed that nurses' assessment of patient's readiness for weaning from MV based on this tool and designed nursing care reduced the duration of MV, re-intubation, and re-connection.